Screening of liver protective effect of ethanolic leaf extract of Callicarpa lanata (EECL) in ethanol induced hepatotoxicity in wister rats - Qadrie, Zulfkar Latief; Balasubramanium, Rajkapoor; Rehman, Shakil U. (International Journal of Basic & Clinical Pharmacology, 2019)
Background: The ethanolic extract of Callicarpa lanata (EECL), belonging to the family Verbenaceae, were studied for hepatoprotective activity in Wister rats with liver damage induced by ethanol. Methods: Ethanol treated rats showed significant increase in the levels of serum enzyme activities, total bilirubin and reduction in total proteins reflecting the liver injury caused by ethanol. EECL, at a dose of 400 and 200mg/kg body weight exhibited hepatoprotective effect by lowering the Serum Glutamate Pyruvate Transaminase (SGPT), Serum Glutamate Oxaloacetate Transaminase (SGOT), Serum Alkaline Phosphate (SALP), Gama Glutamyl Transpeptidase (GGTP), total Bilirubin to a significant extent and also significantly increased the levels of total protein in a dose dependent manner. Results: The results were highly significant at dose level of 400mg/kg body weight (p <0.01) and significant at dose level of 200mg/kg body weight (p <0.05). The effects of EECL at both levels were comparable with standard drug silymarin. The hepatoprotective activity was also supported by histopathological studies of liver tissue. Conclusions: In-vivo hepatoprotective activity of ethanolic leaf extract of Callicarpa lanata (EECL) against Ethanol induced acute liver injury in rats showed significant results in a dose dependent manner.